Pharmacogenetics of the Antiplatelet Effect of Aspirin - Wurtz, Morten; Dalby Kristensen, Steen; Hvas, Anne-Mette; Lerkevang Grove, Erik (Current Pharmaceutical Design, 2012)
The concept of “pharmacogenetics” addresses genetically determined variation in how individuals respond to drugs. Accordingly, specific genetic variants have been suggested as contributors to a reduced response to various antiplatelet drugs. Aspirin is a cornerstone in secondary cardiovascular prevention and has been thoroughly investigated. The efficacy of aspirin is well documented, although with considerable interindividual variation. According to meta-analyses, a reduced antiplatelet effect of aspirin confers an increased risk of cardiovascular events. The platelet response to aspirin is assessed by in vitro evaluation of thromboxane-dependent platelet function. A reduced antiplatelet effect of aspirin can be explained by several mechanisms, which are largely determined by clinical, pharmacodynamic, biological and genetic factors. During the past decade, numerous studies have identified genetic polymorphisms significantly associated with cardiovascular events and modulating the antiplatelet effect of aspirin. However, results have been contradictory allowing only few firm conclusions to be drawn. Polymorphisms in genes encoding glycoproteins (IIb/IIIa, Ia/IIa, VI and Ibα), cyclooxygenases (1 and 2), adenosine diphosphate receptors (P2Y1 and P2Y12) and proteins of importance for haemostasis (thromboxane A2 receptor, coagulation factor XIII, etc.) have been investigated. In particular, a polymorphism in the gene encoding glycoprotein IIb/IIIa has been associated with a reduced antiplatelet effect of aspirin. The additive value of an individual's genetic makeup in predicting the antiplatelet effect of aspirin and the risk of cardiovascular events remains controversial. The present review outlines the pharmacology of aspirin and provides an overview of specific genetic variations considered to influence the antiplatelet effect of aspirin.
Keywords: pharmacogenetics